2010
DOI: 10.1007/s10765-010-0827-4
|View full text |Cite
|
Sign up to set email alerts
|

A New Simplified Local Density Model for Adsorption of Pure Gases and Binary Mixtures

Abstract: Adsorption modeling is an important tool for process simulation and design. Many theoretical models have been developed to describe adsorption data for pure and multicomponent gases. The simplified local density (SLD) approach is a thermodynamic model that can be used with any equation of state and offers some predictive capability with adjustable parameters for modeling of slit-shaped pores. In previous studies, the SLD model has been utilized with the Lennard-Jones potential function for modeling of fluid-so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…The collected data were imported from different works in the literature in order to study the adsorption phenomena of pure gases (CO 2 , CH 4 , and N 2 ), their binary mixtures, and their ternary mixtures on different activated carbons (Table 1). 2,9,33,[54][55][56][57][58][59][60][61][62][63] For each database (DB1, DB2, DB3, DB4, DB5, DB6, and DB7) (Table 2), a set of input variables were identified. For DB1, DB2, and DB3, the inputs were the characteristics of activated carbons (specific surface area and micropore volume), and the operating conditions (temperature and pressure).…”
Section: Database Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…The collected data were imported from different works in the literature in order to study the adsorption phenomena of pure gases (CO 2 , CH 4 , and N 2 ), their binary mixtures, and their ternary mixtures on different activated carbons (Table 1). 2,9,33,[54][55][56][57][58][59][60][61][62][63] For each database (DB1, DB2, DB3, DB4, DB5, DB6, and DB7) (Table 2), a set of input variables were identified. For DB1, DB2, and DB3, the inputs were the characteristics of activated carbons (specific surface area and micropore volume), and the operating conditions (temperature and pressure).…”
Section: Database Collectionmentioning
confidence: 99%
“…2 To avoid these limitations, the application of assumption-free models is proposed. M. Hasanzadeh et al 33 propose a new simplified local density model for adsorption of pure gases and binary mixtures on activated carbon. It was shown that the new SLD model can correlate adsorption data for different pressures and temperatures with minimum error.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation